IMPROVEMENT DESIGN FRONT LADDER PESAWAT DHC - 6 TWIN OTTER 400S DALAM SEGI AERODINAMIS DAN KEKUATAN - Aji Farhan Utomo, (2021)
One of the problems in Indonesia is the difficulty of reaching remote areas for logistics delivery, evacuation missions, or even realizing the tourism sector. Float plane is the solution to this problem. Float aircraft are designed to be able to take off and landing on land as well as water level. One type of float p is the DHC-6 Twin Otter 400S which has tremendous toughness to perform missions in hard-to-access areas. Despite its toughness, failure when the aircraft is operating must certainly be avoided. When the plane lands the impact load is received by the float and passed on the front ladder of the aircraft. This states that the strength of the front ladder must be taken into account because in addition to having to be strong to withstand the pilot's load when boarding the plane, the front ladder must also be able to withstand the impact load. In addition, the performance of the aircraft must not be separated from the aerodynamic design, so in this study was carried out improvement on the front ladder design in terms of aerodynamics using the finite volume method and in terms of strength using finite element methods to result in improvement of front ladder design DHC-6 Twin Otter 400S with aerodynamics and high strength. The results showed that redesign models are more aerodynamic by 34% when the aircraft is in cruise condition and 25% when the aircraft is in take off condition. The redesign model is also 1,263 Kg lighter than the initial model. In addition to being more aerodynamic and lightweight, the redesign model is also able to withstand the same landing load and pilot load carried by the initial model at a strut thickness of 10 mm and ladderstep thickness of 1mm using aluminum material 7075 AMS 4045. Keywords: Float plane, Front ladder,Volume Up Method, Element method up to, Aerodynamics, Strength